Approximating Phosphorus Leaching from Agricultural Organic Soils by Soil Testing. Issue 6 (1st November 2015) - Zheng, Z. M.; Zhang, T. Q.; Kessel, C.; Tan, C. S.; O'Halloran, I. P.; Wang, Y. T.; Speranzini, D.; Van Eerd, L. L.
Abstract : Phosphorus applied to soils in excess of crop requirement could create situations favorable to P enrichment in subsurface flow that contributes to eutrophication of surface water. This pathway of P loss can be more severe in muck (i.e., organic) soils where agricultural production is intensive. This study evaluated the suitability of various environmental and agronomic soil P tests initially designed for mineral soils to predict dissolved reactive P (DRP) in subsurface flow from organic soils. Intact soil columns were collected from 44 muck soils in Ontario to provide a wide range of soil test P levels. A lysimeter leaching study was conducted by evenly adding water in an amount equivalent to 5 mm of rainfall. The leachate DRP concentration was linearly related to soil water‐extractable P and CaCl2 –extractable P with r 2 values of 0.90 and 0.93, respectively, and to Bray‐1 P and FeO‐impregnated filter paper extractable P in a split‐line model with a change point. Mehlich‐3 P and Olsen P, a method recommended for agronomic P calibration in Ontario, were not related to leachate DRP concentration. All P sorption index (PSI) based degree of P saturation (DPS) values were closely related to leachate DRP in split‐line models, with the DPS indices expressed as Bray‐1 P/PSI and FeO‐P/PSI having the highest correlation with leachate DRP concentration. Because it is desirable from practical and economic standpoints that the environmental risk assessment shares the same soil test with agronomic P calibration, the two PSI‐based DPS indices as presented can be considered as environmental risk indicators of DRP subsurface loss from organic soils. Core Ideas: Leaching loss of P in organic soils can be severe, but soil P testing is not available. Leachate DRP was not related to Mehlich‐3 P or Olsen‐P, default soil tests. Leachate DRP was related to P sorption index based DPS in split‐line models. DPS indices Bray1‐P/PSI and FeO‐P/PSI had the highest correlation with leachate DRP. FeO‐DPS can be considered a risk indicator of DRP subsurface loss from organic soils.